pH Effect on Heavy Metal Release from a Polluted Sediment - Yanhao Zhang; Haohan Zhang; Zhibin Zhang; Chengying Liu; Cuizhen Sun; Wen Zhang; Taha Marhaba (Journal of Chemistry)
The performance of Cd, Ni, and Cu release from river sediment at different pH was investigated by a leaching test using deionised water and river water as leachants. Visual MINTEQ geochemical software was used to model the experimental results to predict heavy metal release from sediments. The distribution and speciation of heavy metals in the sediments after leaching test were analyzed by Tessier sequential extraction. Leaching test results showed that the release amounts of Cd, Ni, and Cu are in the range of 10.2–27.3 mg·kg−1, 80.5–140.1 mg·kg−1, and 6.1–30.8 mg·kg−1, respectively, with deionised water as leachant at different pH. As far as the river water was used as the leaching solution in the test, the results show similar metal leaching contents and tendencies to that of the deionised water as leaching solution. The results of Tessier sequential extraction indicate that Cd of residual fraction easily forms obvious precipitate under the acidic condition, especially in the range of pH 0–4 with the residual of Cd over 50% of the total Cd in the sediment. The exchangeable content of Ni decreases with the increase of pH under the range of 0–5. The Fe-Mn oxide fraction of Cu in the sediments changes significantly from pH 0 to pH 9. Based on the effect of pH on the leaching of Cd, Ni, and Cu from the polluted sediment in the tests, more accurate information could be obtained to assess the risk related to metal release from sediments once it is exposed to the changed acid/alkali water conditions.